MATHEMATICAL MODEL OF NON-STSTIONARY THERMO-ELASTIC DEFORMATION OF MULTYLAYER DAMPHING COATINGS IN ELECTRONICS - Mastinovskiy, Y. V. (Radio Electronics, Computer Science, Control, 2015)
Generation of new multilayer coatings of units and blocks in electronics for effective damping of thermo-mechanical impact loads requires the development of mathematical models suitable for engineering practice. Mathematical model and calculation method proposed in this paper allows investigate the passing and reflection of thermo-elastic waves in a multilayer body excited by non-stationary magnetic field at the conductive layer boundary. Also, the problem of estimating relative influence of volume forces induced by the magnetic field in the electrically conductive nonferromagnetic layer on the wave propagation in thermo-elastic polymer compounds was considered. It is assumed that the velocity of heat propagation is finite. Assumptions are introduced to simplify the fully coupled system of magneto-thermo-elastic equations that allow applying the numerical solution based on the method of characteristics for obtaining concrete results. A method for finding required quantities at the nodal points of the boundary between the layers is indicated. The suggested mathematical model and calculation method makes it possible, without making any significant changes in the computing system, to carry out numerical experiments on researching the damping properties of multilayer coatings with different geometrical and mechanical parameters under the conditions of the thermo-mechanical loadings. This calculation method of heterogeneous multilayer thermo-elastic structures can be used to identify the areas most disposed to the damage.